"Okay - let's go over it once more for Hewie's benefit - "[John Hewson at a meeting of the Liberal Party of Orstralia, Woolloomooloo Branch, Rules Committee] - Pryor, Geoff, 1944- (1994)
In a parody of a well-known Monty Python sketch, Opposition Leader John Hewson is 'educated' after he lashes out at some of his more conservative colleagues who express strong opposition to Sydney's Gay Mardi Gras, and all who parade in it.--Information provided by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 4 March 1994.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Hewson, John R. -- Caricatures and cartoons; Liberal Party of Australia -- Caricatures and cartoons; Politicians -- Australia -- Caricatures and cartoons; Australia -- Politics and government -- 1990-2001 -- Caricatures and cartoons